2014
DOI: 10.3109/03009742.2014.910312
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of continuation rates following a switch to subcutaneous methotrexate in rheumatoid arthritis patients failing to respond to or tolerate oral methotrexate: the MENTOR study

Abstract: Treatment with SC MTX results in high continuation rates in patients who fail to respond to or tolerate oral MTX. Consequently, management guidelines should be adapted to include advice that SC MTX should be used before biologic therapy and that MTX failure is defined as failure only when use of SC MTX has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…It acts at multiple points in the inflammatory pathway to improve clinical symptoms and disease control, and treatment adherence is essential for the maintenance of this control (Bello, Perkins, Jay, & Efthimiou, 2017). Subcutaneous (SC) administration has contributed substantially to improving adherence to MTX (Scott, Claydon, & Ellis, 2014). When compared with oral dosing, it offers greater clinical efficacy in both early and long-term disease, and a delay in progression to biological therapy (Bello et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It acts at multiple points in the inflammatory pathway to improve clinical symptoms and disease control, and treatment adherence is essential for the maintenance of this control (Bello, Perkins, Jay, & Efthimiou, 2017). Subcutaneous (SC) administration has contributed substantially to improving adherence to MTX (Scott, Claydon, & Ellis, 2014). When compared with oral dosing, it offers greater clinical efficacy in both early and long-term disease, and a delay in progression to biological therapy (Bello et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies of patients who switched from parenteral to oral MTX demonstrated high rates of flares in disease activity, with increased gastrointestinal side effects 12 13. A recent cohort study of patients taking subcutaneous MTX after oral MTX found high rates of treatment continuation, with 75% of patients still on treatment at 2 years 14. These observational studies, however, were limited by the lack of a comparator group.…”
Section: Introductionmentioning
confidence: 99%
“…Similar data comes from 2 retrospectives studies, where a higher rate of therapy persistence in patients on sMTX than those receiving the drug orally has been observed. 15,17 There are several factors that may explain such good results. Firstly, sMTX is characterized by better tolerance and fewer ADRs.…”
Section: Discussionmentioning
confidence: 99%